Improving bermudagrass in the Southeastern United States with alfalfa as an alternative nitrogen source in grazing systems. Issue 4 (18th January 2023) - Burt, Justin C.; Baxter, Lisa L.; Prevatt, Christopher G.; Kimberly Mullenix, Mary; Stewart, R. Lawton; Tucker, Jennifer J.
Abstract: Background: Bermudagrass ( Cynodon spp.) is one of the most common perennial warm‐season forages grown in the Southeastern United States. The incorporation of alfalfa ( Medicago sativa ) into bermudagrass pastures could serve as an alternative source of nitrogen (N) while also improving the nutritive value of the forage base. Methods: A 2‐year grazing evaluation arranged in a randomized complete block design was conducted from May to September 2018 (Year 1) and May–August 2019 (Year 2) in Tifton, GA, USA. The objective was to compare the production of alfalfa–bermudagrass mixed pastures (BGA) with bermudagrass monoculture pastures with (BGN) or without (BG) the application of synthetic nitrogen on forage production and stocker cattle performance. Results: Differences were observed for average daily gain ( p = 0.10), gain per hectare ( p = 0.02) and stocking rate ( p = 0.01), in that BGA was greatest compared to BGN and BG, which did not differ from each other. Furthermore, BGA had increased forage crude protein ( p = 0.01) and total digestible nutrients ( p = 0.01) compared to BGN and BG. Finally, BGA provided the greatest economic return per hectare compared to BG or BGN. Conclusions: These data illustrate improved animal performance and forage nutritive value using alfalfa–bermudagrass systems and offer a viable option for producers seeking alternatives to synthetic N sources for bermudagrass pastures in the Southeastern United States. Abstract : Alfalfa‐bermudagrass mixture under rotational grazing in Tifton, GA 2018.